Exploring the Nexus between the Absorptive Capacity, Corporate Sustainability, Supply Chain Agility and Manufacturing Firm Performance - Chanicha Moryadee; Kiatkulchai Jitt-Aer (International Journal of Supply Chain Management, 2020)
The study has intended to examine the absorptive capacity on the firm performance of the Indonesian firms. The study has also examined the mediating effect of SC agility in the relationship between the absorptive capacity and the firm performance. Lastly, the study has examined the mediating role of corporate sustainability in the relationship between the absorptive capacity and the firm performance. The data is collected from the middle managers of the mining firms in Indonesia. the authors have employed the convenient sampling. The authors have distributed in total the  320 questionnaires. The response rate of the current study is 67 percent. The influence of SC agility as a mediator has been analyzed between absorptive capacity and performance of the firm. It was found by the study that SC agility fully mediates the relation between absorptive capacity and performance of the firm. The literature on competitiveness of SC has been improved by adding empirical evidence. Moreover, there is need to leverage both absorptive capacity and SC agility to improve the performance of a firm. It has been suggested by results that superior performance could be achieved transformation of absorptive capacity through SC agility. The companies are responsible for the influence on society and environment that occurs because of their actions. The companies are responsible for the influence on society and environment that occurs because of their actions. The corporate activities not just influence the company itself rather, it affects the whole SC and society. The corporate activities not just influence the company itself rather, it affects the whole SC and society.